PENGARUH PROFITABILITAS, STRUKTUR MODAL, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Veronica, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to obtain empirical evidence about the effect of profitability, capital structure, liquidity, and company size on the value of companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. This study uses data from financial statements published on the official website of the IDX. The results of this study indicate that capital structure has a significant positive effect on firm value. But other variables such as profitability, liquidity and firm value do not have a significant negative effect on firm value. To improve further research, it is expected to use a sample of companies from other sectors besides manufacturing, add a number of samples by extending the study period, and use other independent variables.